Decision Support System for Best Supplier Selection Using Simple Additive Weighting and Rank Sum Weighting - A. Ferico Octaviansyah Pasaribu (PT. Tech Cart Press, 2023)
Decision Support System or DSS is a computer system designed to help make complex and problem-oriented decisions. SAW method is one of the methods used in multi-criteria decision making to sort and select alternatives based on an assessment of several criteria. The SAW method uses a simple summation approach of weighted weights assigned to each criterion. Rank sum weighting is one method used in decision support systems to sort alternatives based on assessments on specific criteria. The results of this study are the selection of the best suppliers using the simple additive weighting method and applying the rank sum weighting model in determining the weight of the criteria used, namely price, product quality, delivery time, packaging form, and the number of shipments. Ranking results for rank 1 were obtained by Supplier B with a value of 0.846, for rank 2 were obtained by Supplier E with a value of 0.837, for rank 3 were obtained by Supplier C with a value of 0.787, for rank 4 were obtained by Supplier A with a value of 0.723, for rank 5 were obtained by Supplier B with a value of 0.698.